Doença de Alzheimer: estudos sobre acurácia diagnóstica nos pacientes em uso de anticolinesterásicos e a percepção dos familiares quanto aos seus benefícios - Piovesana, Magda Cristina Flaitt Sanches (2010)
This study was realized in the Neurogeriatrics Clinic Base Hospital of Medicine Faculty in Sao Jose do Rio Preto. Objective: To study the diagnostic accuracy in Alzheimer's disease in patients treated with cholinesterase inhibitors available by Pharmacy of Exceptional Medicines and verify the impact of this therapy by the perception of families or caregivers. Methods: Cross-sectional study (prospective) the sample selection was random, in the period between May 2008 and February 2010. The certification of the diagnosis of Alzheimer's disease followed NINCDS-ADRDA, complemented by Scale Clinical Evaluation of Dementia (CDR), Scale for the Assessment of Disability in Dementia (DAD) and interviews with family and / or caregiver (structured questionnaire). Statistically used - to cross-frequency tables, chi-square test, Fisher exact test, Kruskal-Wallis test, t-test and principal component analysis, a significance level of 5%. Results: Participants 106 patients, categorized into Group MC, when met criteria for AD and the DNMC when not fulfilled. In the MC Group was observed, higher age (mean 78anos), 85% of patients with MMSE lower than expected, worse performance on the DAD (median 25), according to the severity 37% were in the mild stage, 48% at moderate and 15% at severe stage, the treatment time was larger and in full doses of anticholinesterase. In the DNMC Group ages were younger (mean 74anos), 50% of patients with MMSE lower than expected, better performance in the DAD (median 75) with less treatment time and at subtherapeutic doses. In EQ, in relation to the memory of the MC Group all patients showed a deficit, 18% improved and 54% worsened; 13% in the DNMC Group showed no deficit, 48% improved and 13% xii worsened. In the assessment of temporal orientation in the MC group, 8% of the patients had no disorientation, 8% improved and 62% worsened, since the DNMC Group, 37% had no disorientation, 30% improved and 16% worsened. In Topographical orientation, in the patients in MC Group, 77% did not go out alone and in the DNMC Group 54% had no difficulty in orienting themselves. In the MC Group, 14 of the 15 neuropsychiatric symptoms were more often, only depression was higher in the DNMC. In carrying out activities of daily living, patients of MC Group worsened in all the items in relation to the DNMC Group. Conclusions: It was observed that 51% of patients using anticholinesterases did not meet criteria for the diagnosis of AD likely, older age was associated with the MC Group, which had downgraded MMSE, worse performance in DAD and in the QE. In Structured Questionnaire the patients of DNMC Group showed a different behavior, perhaps by having other diagnoses, presented better performance.